Práctica de las 5S para el mejoramiento de los procesos para la microempresa láctea DON PATO. - Espinoza Cevallos, Ismael Eduardo (2018)
The purpose of this research project is to improve the processes for the dairy micro-company "Don Pato", to implement the 5S and improve productivity through the collection of information and thus meet the demands and expectations of the client; due to competitive pressures and technical advances that identified several problems of industrial organization that have caused the activity to be unsuccessful, such as: the delay in the response to the client, delay in the delivery of orders, lack of cleanliness in certain areas of work and the disorganization of the warehouses of raw material and finished product. An information survey was carried out: time, photos, observation, interview and survey, therefore the criteria and theoretical requirements for the 5S and quality management were identified, the situation of the PYME was diagnosed and the practice of This methodology in production processes through qualitative and quantitative field research, documentary-bibliographic and descriptive, through techniques and diagrams such as: Pareto diagram, cause-effect diagram, Ishikawa, flow charts, etc. With the improvement proposal it was possible to reduce downtime and also that by practicing this 5S methodology it is possible to improve in 42.5% the time invested in the elaboration of yogurt and in 62.3% in the cheese; 5S instructions were also made available to improve the industrial development of the microenterprise, with this practice it is sought that the microenterprise obtains a philosophy of continuous improvement, quality, safety and optimal working climate to improve the processes of dairy production.